Application of the Chinese Version of the Pittsburgh Sleep Quality Index in People Living With HIV: Preliminary Reliability and Validity - Yan, Dong-Qin; Huang, Yun-Xiang; Chen, Xi; Wang, Min; Li, Jie; Luo, Dan (Frontiers in Psychiatry, 2021)
Background: The Pittsburgh Sleep Quality Index (PSQI) has been a widely-used instrument measuring the sleep quality among people living with HIV (PLWH) in China while its psychometric properties have yet to be examined in this population. We aimed to assess the reliability, validity of the Chinese-version of PSQI in PLWH and identify factors associated with sleep quality. Methods: This study was based on a longitudinal study of newly diagnosed PLWH, among whom the PSQI was used to measure sleep quality 5 years after HIV diagnosis (n = 386). To evaluate internal consistency, Cronbach's alpha and corrected item-total correlation were calculated. To assess construct validity, Pearson’s correlation coefficients were calculated between PSQI scores and depression, anxiety, stress and health-related quality of life (HRQoL). Known group validity was evaluated by comparing PSQI scores between participants with probable depression and those without. Binary logistic regression was conducted to identify factors associated with sleep disturbances. Results: The internal consistency Cronbach’s alpha for the Chinese-version of PSQI in PLWH was 0.713. Construct validity was established by significant relationships between PSQI and depression, anxiety, stress and HRQoL. The PSQI scores in participants with probable depression were significantly higher than those without, indicating a good known-group validity. Sleep disturbances were associated with less income, higher CD4 counts, antiretroviral treatment (ART) initiation, exercise, depression and higher stress levels. Conclusions: The Chinese-version of PSQI is feasible for use among Chinese PLWH. Over a third PLWH reported sleep disturbances. More attention should be given to individuals with less income and on ART. Intervention aimed at improving mental health or facilitating exercise may improve the sleep quality.